(untitled) (Jurnal Teknologi (Sciences & Engineering), 2024)
Globally, the rapid emergence of antibiotic-resistant bacteria poses a major threat to public health, threatening the effectiveness of antibiotics. Addressing the crisis of antimicrobial resistance requires urgency in new drug discovery and the effort in finding novel compounds is dramatically evolving. However, one of the main obstacles is the rediscovery of known compounds from natural resources. To overcome this challenge, exploring underexploited location for new resource of actinomycetes, such as Beach Ridges Interspersed with Swales (BRIS) soil in Malaysia, was selected. Soil samples from Jambu Series and Rudua Series in Setiu, Terengganu were collected and analysed. A total of 87 actinomycetes strains were isolated on yeast malt agar (ISP2), Actinomyces agar and Zobell marine agar, with the highest number from the Jambu series using serial dilution and spread plate method. Antimicrobial screening revealed that 31 isolates exhibited activity against ESKAPE pathogens, with 28 and 12 isolates showing activity against Gram-positive and Gram-negative bacteria, respectively. These isolates showed strong inhibiting response towards one or more ESKAPE pathogens. This study highlights the potential of BRIS soil as an underexploited habitat for discovering actinobacterial communities which could lead to the discovery of a new potential antimicrobial producer to serve as novel drug leads.